A Programmable Differential Transimpedance Amplifier for Capacitive MEMS Accelerometers - Royo, Guillermo; Gimeno, Cecilia; Aldea, Concepción; Celma, Santiago (Jornada de Jóvenes Investigadores del I3A, 2017)
In this work, a fully-differential transimpedance amplifier with programmable gain and bandwidth for MEMS accelerometers is presented. It is aimed for a differential surface-micromachined combfinger capacitive accelerometer, but can be used in many other capacitive sensor applications.